الصناعة السورية وإمكانية الاستفادة من تجربة التصنيع في كورية الجنوبية لتطويرها (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن تجربة كورية الجنوبية جذبت انظار العالم اليها، حيث انتقلت من قائمة أفقر بلدان العالم الى تصنيفها دولة صناعية و حققت معدلات نمو عالية بعد عمليات الاصلاح الاقتصادي التي قامت بها، حيث استطاعت جذب الاستثمارات اليها وحققت زيادة في صادراتها وخلق فرص العمل بالإضافة الى نمو ناتجها المحلي وركزت على التعليم والانفتاح على العالم الخارجي واستخدام التكنولوجيا العالية والادارة السليمة الواعية وتشجيع البحوث العلمية التطبيقية وعلى الرغم من اتباعها سياسة احلال الواردات وتوفير الحماية اللازمة لصناعتها الوطنية الا ان هذه الصناعة كانت مرهونة بتحقيق معايير اقتصادية معينة اما سياستها التجارية فقد اتسمت بالاتجاه التدريجي الى تحرير التجارة مع العمل على توفير الدعم المؤسسي للصادرات. ونظراً لأهمية الصناعة ودورها في عملية النمو الاقتصادي فقد تم دراسة واقع الصناعة السورية واهم الخطوات المتخذة لتطويرها وخاصة التركيز على الصناعات التصديرية، وجذب الاستثمارات الصناعية وتحسين بيئة العمل القانونية والتشريعية بالاستفادة من نقاط نجاح التجربة الكورية واهمها التركيز على الميز ة النسبية ووضع استراتيجية صناعية يتم فيها تحديد الصناعات ذات الأولوية وفق الميزة النسبية التي تتمتع بها. The South Korean experience attracted the attention of the world, moving from the list of the poorest countries to the classification of an industrialized country and achieved high growth rates after the economic reforms carried out by attracting investment and increased exports and job creation in addition to the growth of domestic output And focused on education and openness to the outside world and the use of high technology and sound management conscious and promote applied scientific research and despite the adoption of the policy of importing imports and provide protection for the national industry, but the industry was subject to the achievement of standards Economic policy, while its trade policy has been characterized by a gradual trend towards trade liberalization while working to provide institutional support for exports. In view of the importance of the industry and its role in the process of economic growth, the study of the reality of the Syrian industry and the most important steps taken to develop it, especially the focus on export industries, attracting industrial investments and improving the legal and legislative working environment were based on the success of the Korean experience. Priority industries according to their comparative advantage.